2016
DOI: 10.1007/s12206-016-0715-3
|View full text |Cite
|
Sign up to set email alerts
|

Generation of electrical energy using lead zirconate titanate (PZT-5A) piezoelectric material: Analytical, numerical and experimental verifications

Abstract: Energy harvesting is the process of attaining energy from the external sources and transforming it into usable electrical energy. An analytical model of piezoelectric energy harvester has been developed to determine the output voltage across an electrical circuit when it is forced to undergo a base excitation. This model gives an easy approach to design and investigate the behavior of piezoelectric material. Numerical simulations have been carried out to determine the effect of frequency and loading on a Lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…where b a f f f D = -A recently proposed electrical power method for calculating mechanical quality factor showed that the maximum mechanical quality factor occurs between resonance and anti-resonance frequencies while the previous methods (impedance and burst) were limited to provide the mechanical quality factor only at resonance and anti-resonance frequencies [22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…where b a f f f D = -A recently proposed electrical power method for calculating mechanical quality factor showed that the maximum mechanical quality factor occurs between resonance and anti-resonance frequencies while the previous methods (impedance and burst) were limited to provide the mechanical quality factor only at resonance and anti-resonance frequencies [22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…FMLs show fatigue crack growth life 17 times longer than monolithic Al plates even at higher loads. 28 FCGRs of FMLs can be predicted by using analytical methods, 29,30 phenomenological methods 31,32 , finite element techniques 22,[33][34][35][36][37] and boundary element methods. Analytical models 28 used to describe the crack growth behaviour of FMLs are preferred by aircraft designers, but accurate development and validation of these analytical models require both experimental validation and finite element method verification.…”
Section: Introductionmentioning
confidence: 99%
“…This simulation adapted the material parameters of P-5A for the piezoelectric transducer thin film, which is an industry type 5A (Navy type II) piezoelectric ceramic [35], listed in Table 2. For the simulation, the pattern of the Au topside electrode with a thickness of 0.15 µm was considered, while the buffer layers were ignored.…”
Section: Resultsmentioning
confidence: 99%